2020
DOI: 10.36660/abc.20200381
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Comparativo da Doença Coronariana Microvascular Causada por Doença de Chagas e por Outras Etiologias

Abstract: Fundamento: A doença de Chagas (DC) constitui uma causa potencial negligenciada de doença microvascular coronariana (DMC). Objetivos: Comparar pacientes com DMC relacionada à DC (DMC-DC) com pacientes com DMC ligada a outras etiologias (DMC-OE). Métodos: De 1292 pacientes estáveis, encaminhados para angiografia coronária invasiva para elucidar o padrão hemodinâmico e a causa de angina, 247 apresentaram coronárias subepicárdicas normais, e 101 foram incluídos após aplicação dos critérios de exclusão. Desses, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…In endemic countries, it represents one of the main causes of non-ischemic cardiomyopathy, heart failure, and sudden death (Lima et al, 2021) [ 36 ]. In a study of stable chronic Chagas disease patients suspected of having Chagas microvascular coronary disease, just over 33% had normal ECG results, concluding that alterations in this exam are frequent when patients have cardiac complications (Campos et al, 2020) [ 37 ], which were absent in the patients studied in this research.…”
Section: Discussionmentioning
confidence: 75%
“…In endemic countries, it represents one of the main causes of non-ischemic cardiomyopathy, heart failure, and sudden death (Lima et al, 2021) [ 36 ]. In a study of stable chronic Chagas disease patients suspected of having Chagas microvascular coronary disease, just over 33% had normal ECG results, concluding that alterations in this exam are frequent when patients have cardiac complications (Campos et al, 2020) [ 37 ], which were absent in the patients studied in this research.…”
Section: Discussionmentioning
confidence: 75%
“… 88 , 112 114 In a recent prospective study from Brazil, it was found that 15% of patients referred for diagnostic coronary angiograms had CD, with most of them not having evidence of obstructive epicardial coronary artery disease. 115 …”
Section: Microvascular Remodeling In Ccmmentioning
confidence: 99%
“…88,[112][113][114] In a recent prospective study from Brazil, it was found that 15% of patients referred for diagnostic coronary angiograms had CD, with most of them not having evidence of obstructive epicardial coronary artery disease. 115 Several studies have demonstrated both reversible and fixed MPD at various stages of CCM. 116,117 Additionally, in patients with CCM and malignant ventricular arrhythmias, MPD regions have demonstrated local myocardial sympathetic denervation.…”
Section: Evidence Of Microvascular Remodeling Derangements From Clini...mentioning
confidence: 99%
“… 33 Estima‐se que 20‐40% dos pacientes com cardiopatia chagásica tenham angina atípica decorrentes de anormalidades na perfusão miocárdica provocadas pelo exercício e reversíveis com o repouso, provavelmente associadas com isquemia microvascular. Campos et al 34 compararam pacientes com isquemia microvascular relacionada à doença de Chagas com pacientes com isquemia microvascular decorrentes de outras etiologias. Concluíram que os dois grupos tiveram características clínicas, hemodinâmicas e de perfusão miocárdica semelhantes, mas a disfunção global e segmentar do ventrículo esquerdo foi mais grave nos pacientes com isquemia microvascular relacionada com a doença de Chagas.…”
Section: Insuficiência Cardíaca E Cardiomiopatiaunclassified
“…Análise de >100.000 Cirurgias Cardiovasculares Realizadas no Instituto do Coração e a Nova Era com foco nos resultados http://abccardiol.org/wp‐content/uploads/articles_xml/0066‐782X‐abc‐S0066‐782X2020000400603/0066‐782X‐abc‐S0066‐782X2020000400603‐pt.x64000.pdf Alves 22 5. Hospitalização por infarto agudo do miocárdio: um registro de base populacional http://abccardiol.org/wp‐content/uploads/articles_xml/1678‐4170‐abc‐115‐05‐0916/1678‐4170‐abc‐115‐05‐0916.x64000.pdf Campos 34 6. Estudo comparativo da doença coronariana microvascular causada por doença de Chagas com outras etiologias http://abccardiol.org/wp‐content/uploads/articles_xml/0066‐782X‐abc‐115‐06‐1094/0066‐782X‐abc‐115‐06‐1094.x64000.pdf Stefan 32 7.…”
Section: Introductionunclassified